Decontamination Effect of Zinc Oxide Nanoparticles, Rosmarinic Acid and Anatolian Propolis on Foodborne Bacteria - Tahsin Onur Kevenk; Zeki Aras (Turkish Journal of Agriculture: Food Science and Technology)
Zinc oxide (ZnO) has been used in the pharmaceutical, cosmetic, paint, textile, and food industries to coat surfaces and absorb UV rays. As a result of its antimicrobial properties in nanoscale, it may be a promising chemical for decontamination. Zinc oxide nanoparticles (ZnO-NPs) are generally considered safe (GRAS) for their stability under challenging processing conditions. Our study investigated the antimicrobial activities of rosmarinic acid and propolis, prepared at different concentrations together with ZnO-NPs. For this purpose, six leading foodborne pathogens and a starter culture were chosen. The invitro decontamination effects of ZnO-NPs, rosmarinic acid, and propolis combinations on selected bacteria in the first 24 hours were demonstrated by bacterial counts at regular intervals. According to our results, propolis and ZnO-NPs showed remarkable results together. In addition, rosmarinic acid’s lower concentrations were also found to induce the decontamination effect of ZnO-NPs. Although the antimicrobial effect of ZnO-NPs, when used alone, was less than when used in combination, it was still found to be sufficient.